International Accounting Standards in Africa: Selective Recursivity for the 'Happy Few'?. Issue 4 (29th November 2017) - Botzem, Sebastian; Quack, Sigrid; Zori, Solomon
Abstract: This study explores recursivity in international accounting standard‐setting, focusing on participation of actors from African countries. While the International Financial Reporting Standards (IFRS) Foundation bases its legitimacy claims as a global standard‐setter on a combination of expertise and a formally transparent set of recursive procedures for consultation of stakeholders, empirical results show that participation in the latter is geographically very uneven. The article argues that conceptual mismatch between the standard‐setter's objectives on the one hand and the socio‐economic, cultural and political conditions in many African countries on the other leads to selective recursivity that is problematic for the former's legitimacy and effectiveness. These findings are of wider relevance for debates on global standard‐setting and development. Abstract : Representation in decision‐making bodies and participation in feedback remains highly skewed towards developed countries with African countries conspicuously underrepresented or missing.